Ipilimumab Real-World Efficacy and Safety in Korean Melanoma Patients from the Korean Named-Patient Program Cohort - Jung, Minkyu (Cancer Res Treat, 2017)
PURPOSE: Ipilimumab improves survival in advanced melanoma patients. However, the efficacy and safety of ipilimumab has not been evaluated in Asian melanoma patients with a high frequency of mucosal and acral melanoma subtypes. MATERIALS AND METHODS: Advanced melanoma patients treated with 3 mg/kg ipilimumab in a Korean multicenter named-patient program (NPP) were evaluated between September 2014 and July 2015. Baseline characteristics and blood parameters including neutrophil to lymphocyte ratio (NLR) were assessed, and outcome and adverse events were evaluated according to subtypes. RESULTS: A total of 104 advanced melanoma patients were treated. The primary sites were acral (31.7%), mucosal (26%), cutaneous (26%), uveal (9.6%), and unknown (6.7%). Sixty-eight patients (65.4%) experienced adverse events, and the most common toxicity was skin rash (22.1%), 10 patients (9.6%) experienced adverse events of grade 3 or higher. The median progression-free survival (PFS) was 2.73 months (95% confidence interval, 2.67 to 2.85), and there was no difference in PFS according to subtypes. Poor performance status, liver metastasis, and NLR (≥ 5) were independent poor prognostic factors by multivariate analysis. CONCLUSION: In the Korean NPP cohort, ipilimumab showed similar efficacy and tolerability compared to Western patients, regardless of subtypes. All subtypes should benefit from ipilimumab with consideration of performance status, liver metastasis, and NLR.